The Moral Foundations of Desired Cultural Tightness - Di Santo, Daniela; Gelfand, Michele J.; Baldner, Conrad; Pierro, Antonio (Frontiers in Psychology, 2022)
People vary on their desire for strict norms, and the moral underpinnings of these differences have yet to be explored. The current research examined whether and how moral beliefs held by individuals would affect the extent to which they want their country to be tight (i.e., having strict social norms) or loose (i.e., having more permissive social norms). In particular, the effects of the “binding” and “individualizing” foundations, which are moral beliefs focused on the importance of groups and individuals, respectively, were examined. We hypothesized that the binding foundations could predict people’s desire for cultural tightness. We also hypothesized that the perception that one’s society is threatened may drive this effect. Three studies were conducted using both cross-sectional (Studies 1 and 3) and two-wave (Study 2) designs. Demographic variables and participants’ political orientation effects were controlled. In Study 1, only the binding foundations significantly predicted higher desired tightness. In Study 2, binding foundations predicted desired tightness measured at follow-up. In Study 3, the positive effect of perceived threat on desired tightness via the binding foundations was confirmed. From additional within-paper analyses we also have some evidence of significant relationships, albeit unstable across studies, between desired tightness and individualizing foundations.